Ideal invisibility cloak for electrostatic field - Chua, Jia Jun (Nanyang Technological University, 2022)
Invisibility cloak is a fictional device which can make objects invisible to outer detection. Recent years, invisibility cloak has become a hot research topic and widely explored in the literature. However, up to date, experimental realization of ideal invisibility cloaks still remain a challenge. Nearly all previous schemes make simplifications, and hence the cloaks realized suffer from large scattering. In this project, we will explore a transformation invariant approach to realize ideal invisibility cloaks. As a specific example, the student will be guided to design an ideal invisibility device that can smoothly redirect electric fields around an obstacle. Possible experimental implementation will explored if time allows.